2016
DOI: 10.1073/pnas.1522551113
|View full text |Cite
|
Sign up to set email alerts
|

Causal evidence for frontal cortex organization for perceptual decision making

Abstract: Although recent research has shown that the frontal cortex has a critical role in perceptual decision making, an overarching theory of frontal functional organization for perception has yet to emerge. Perceptual decision making is temporally organized such that it requires the processes of selection, criterion setting, and evaluation. We hypothesized that exploring this temporal structure would reveal a large-scale frontal organization for perception. A causal intervention with transcranial magnetic stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
193
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 178 publications
(226 citation statements)
references
References 46 publications
28
193
5
Order By: Relevance
“…The model assumes that the information available for metacognition is corrupted by extra noise compared to the information available for the perceptual decision. Several previous papers have proposed similar architecture (Berg & Ma, 2016;De Martino et al, 2013;Jang et al, 2012;Maniscalco & Lau, 2016;Mueller & Weidemann, 2008;Rahnev et al, 2016). Here we tested a strong, and previously unrecognized, prediction of hierarchical models on the relationship between sensory noise and metacognitive efficiency.…”
Section: Discussionmentioning
confidence: 77%
“…The model assumes that the information available for metacognition is corrupted by extra noise compared to the information available for the perceptual decision. Several previous papers have proposed similar architecture (Berg & Ma, 2016;De Martino et al, 2013;Jang et al, 2012;Maniscalco & Lau, 2016;Mueller & Weidemann, 2008;Rahnev et al, 2016). Here we tested a strong, and previously unrecognized, prediction of hierarchical models on the relationship between sensory noise and metacognitive efficiency.…”
Section: Discussionmentioning
confidence: 77%
“…Whether this functional differentiation is idiosyncratic to perceptual decision making or directly relates to other cognitive functions, such as cognitive control of actions, is an intriguing question for future research. The current study by Rahnev et al (1) thus paves the way for new avenues of research that investigate the functional differentiation among frontal regions across cognitive domains. Moreover, the study will serve as a starting point for research into the relationship between the neural mechanisms of basic perceptual decisions and those neural mechanisms underlying other forms of decision making, such as value-based or social decisions (3,9).…”
mentioning
confidence: 70%
“…This everyday example shows that a complex cascade of events must occur in our brains between the registration of a stimulus by our sensory systems and the potential action that we take in response to this stimulus. A study by Rahnev et al (1) in PNAS investigates the neural mechanism underlying this decision process. The results suggest distinct functional roles of different regions in the frontal lobe in the attentional selection of stimuli, in setting a criterion for the speed-accuracy tradeoff, and in confidence judgments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on only valid data, both the Rounis and Bor et al studies found a null result. In addition, the Ruby et al paper cites a relevant recent TMS prefrontal cortex metacognition paper by Rahnev and colleagues (Rahnev, Nee, Riddle, Larson, & D'Esposito, 2016), where TMS to prefrontal cortex actually enhanced perceptual metacognition. Ruby and colleagues conclude that these results "suggest that different parts of DLPFC perform different [metacognitive] functions."…”
Section: Issues With the Bayesian Assumptionsmentioning
confidence: 99%